Discourse marking in Burmese and English: a corpus-based approach - Hnin Tun, San San (2006)
This study is a comparative analysis of discourse marking systems in Burmese and in English, using a corpus-based approach within the framework of discourse analysis. The focus of this study is a set of lexical items in a particular word class called 'particles' in Burmese, which lack one-to-one equivalents in English and are characterized by highly context-dependent semantic values. Unlike traditional comparative studies involving less commonly studied languages that tend to base their analyses on the model of well-established linguistic systems such as English, this study is Burmese-originated. It starts out with an identification of discourse functions typically associated with high frequency Burmese particles, and their equivalent realisations in English are subsequently identified. Findings indicate that Burmese particles share common cross-linguistic characteristics of discourse markers as described in the current literature. The data offers clear evidence that discourse functions of Burmese particles investigated are commonly found in spoken English, but they are not realised through the same discourse marking system. This study therefore calls for a more effective comparative methodology that can compare syntactically-oriented discourse marking systems more effectively with lexically-oriented ones, such as in the case of Burmese and English respectively. Last but not least, this study also challenges the notion of 'word' as a unit of analysis for a corpus-based approach, as the notion of word cannot be easily defined in a syllabic language such as Burmese.